Characterization of the novel HLA‐DPB1*1359:01 allele by next generation sequencing. (20th September 2022) - Jacob, Valentine; Desoutter, Judith; Guillaume, Nicolas
Abstract : HLA‐DPB1*1359:01 differs from HLA‐DPB1*03:01:01 by one nucleotide substitution in codon 77 in exon 2.